Adubação nitrogenada e densidade de semeadura em soja - Uhry, Daniel (2010)
In cultivars with a cycle shorter than 120 days it is known that there is a relationship between the speed of canopy closure and the grain yield. Aiming at a better initial growing and consequently a quickest canopy closure the aim of this study was to determine the effect of starting rates in genetically modified soybean cultivars in the late sowing and with a cycle shorter than 120 days. Experiments have been performed during the 2009 late sowing in Santa Maria, RS, Brazil. The cultivars used were A 6001 RG, FUNDACEP 53RR and BMX Apolo RR in the sowing density of 250 and 500 thousand viable seeds ha-1. The applied nitrogen rates were 0, 15 and 30 kg of N ha-1 as urea. The experimental design was randomized blocks with four replications with cultivars in the main plot and sowing density in the subplots and nitrogen rates in the sub-subplots. The covering rate was evaluated in two different periods of the cycle, in the full flowering and grain filling period, yield components and grains yield. It was not possible to show the effect of the starting rate for any of the cultivars in the tested conditions. For the yield variable there were differences between populations and cultivars. In the average of the three cultivars the population of 500.000 plants ha-1 showed better productivity with 3068 kg versus 2821 kg ha-1 in 250.000. On the other hand, among the cultivars, FUNDACEP 53RR obtained better yield followed by BMX Apolo RR and A 6001 RG. The right choice of the genotype with more suitable sowing is fundamental for soybean to obtain higher yields in the late sowing in Rio Grande do Sul.